Online Monitoring of Capacitors in Power Converters - Buiatti, Gustavo M.; Martín-Ramos, Juan A.; Martínez, Juan A.; Amaral, A. M. R.; Cardoso, A. J. Marques (Eletrônica de Potência, 2011)
In power converters, the filtering or DC link capacitors are usually the component with shorter lifetime. With the aging, both, electrolytic and film capacitors, do often burst out, causing serious damages or even the destruction of the whole power stage. In this paper, a technique for diagnostic purposes is presented to estimate online, and even in real time, the aging of capacitors in different converters. The technique is based on the estimation of the capacitors equivalent series resistance (ESR) and capacitance. In this way, predictive maintenance can be carried out, and it is possible to alarm for the capacitor replacement before failure. In order to demonstrate and validate the effectiveness and accuracy of the proposed technique, several power topologies are discussed, showing experimental results. An embedded prototype with the real- time estimation through a Digital Signal Processor (DSP) is constructed and presented.